Cyclic AMP Represents a Crucial Component of Treg Cell-Mediated Immune Regulation - Klein, Matthias; Bopp, Tobias (Frontiers in Immunology, 2016)
T regulatory (Treg) cells are one of the key players in the immune tolerance network (ITN) and a plethora of manuscripts has described their development and function in the course of the last two decades. Nevertheless, it is still a matter of debate which mechanisms and agents are employed by Treg cells, providing the basis of their suppressive potency. One of the important candidates is cyclic AMP (cAMP) which is long known as a potent suppressor at least of T cell activation and function. While this suppressive function by itself is widely accepted the source and the mechanism of action of cAMP are less clear and a multitude of seemingly contradictory data allow for in principle two different scenarios of cAMP-mediated suppression. In one scenario Treg cells contain high amounts of cAMP and convey this small molecule via gap junction intercellular communication (GJIC) directly to the effector T cells (Teff) leading to their suppression. Alternatively, it was shown that Treg cells represent the origin of considerable amounts of adenosine which trigger the adenylate cyclases (AC) in Teff via A2A and A2B receptors thus strongly increasing intracellular cAMP. This review will present and discuss initial findings and recent developments concerning the function of cAMP for Treg cells and its impact on immune regulation.